USE OF ELEMENTS OF RATIONAL ATTRACTION IN TELEVISION ADVERTISING (Marketing Journal, 2025)
The article analyzes the importance, types and application of rational appeal elements in television advertising with examples. Rational appeals are classified based on comparative, one-sided and two-sided messages, and their effectiveness in promoting brands is considered. The study analyzes the advertising strategies of such well-known brands as BMW, Tide, Nestle, Oral-B, and also emphasizes the influence of advertising objectives, audience psychology and product characteristics on the selection of rational appeals.
Keywords: television advertising; rational appeal; comparative message; one- way message; two-way message; brand image